2020
DOI: 10.21037/atm-20-3745
|View full text |Cite
|
Sign up to set email alerts
|

The GABRG2 F343L allele causes spontaneous seizures in a novel transgenic zebrafish model that can be treated with suberanilohydroxamic acid (SAHA)

Abstract: Background: Mutations in the γ-aminobutyric acid type A (GABA A ) receptor γ2 subunit gene, GABRG2, have been associated frequently with epilepsy syndromes with varying severities. Recently, a de novo GABRG2 mutation, c.T1027C, p.F343L, was identified in a patient with an early onset epileptic encephalopathy (EOEE). In vitro, we demonstrated that GABA A receptors containing the mutant γ2(F343L) subunit have impaired trafficking to the cell surface. Here, we aim to validate an in vivo zebrafish model of EOEE as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype. 29,30 Moreover, gabrg2 −/− zebrafish mutants are prone to light-induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype. 29,30 Moreover, gabrg2 −/− zebrafish mutants are prone to light-induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 64%
“…Most Sunflower syndrome patients have difficult to treat epilepsy, which could also be the case for our patient although longer follow‐up is needed to confirm this constellation. Preclinical studies showed that zebrafish overexpressing mutant human GABRG2 (p.(Phe343Leu)) subunits mimicked the human DEE phenotype 29,30 . Moreover, gabrg2 −/− zebrafish mutants are prone to light‐induced seizures and respond well to VPA 31 ; mimicking the phenotype and drug response of our patient.…”
Section: Discussionsupporting
confidence: 52%
“…To detect the effect of locations of mutations on phenotypes, we compared the locomotive activity of different mutant GABRG2 transgenic zebrafish. In the previous research, we generated F343L and I107T transgenic zebrafish with spontaneous seizures 6,10 . In this research, the distance traveled in 30 min at 5 dpf was compared in the above three transgenic lines and the data showed that all mutant zebrafish traveled more than the WT control group, showing an epileptic phenotype.…”
Section: Resultsmentioning
confidence: 93%
“…HOXC9 controls various cellular processes linked to differentiation via activating and repressing the transcription of different gene sets (41). Mutations in GABRG2 have been associated with epilepsy syndromes with varying severities (42). CALB2 is expressed in most poorly differentiated colon carcinomas (43).…”
Section: Discussionmentioning
confidence: 99%